Hepatitis A epidemic in men who have sex with men (MSM) in Milan, Italy : Hepatitis A epidemic in MSM in Milan - Aulicino, Gianuario; Faccini, Marino; Lamberti, Anna; Senatori, Sabrina; Ciconali, Giorgio; Gandolfi, Cecilia; Galli, Cristina; Tagliacarne, Catia; Castaldi, Silvana; Romanò, Luisa (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Hepatitis A is an infectious disease characterized by fecal-oral transmission; however, a rise in sexually-transmitted cases has been observed, particularly among “men who have sex with men”. In Europe, a Hepatitis A epidemic occurred among men who have sex with men between 2016 and 2018. The aim of this study is to describe this Hepatitis A epidemic in the city of Milan and to analyze the incidence of Sexually Transmitted Diseases co-infection among Hepatitis A cases. Methods: Hepatitis A cases were traced and identified. Epidemiological data were collected and Hepatitis A vaccination was investigated. Cases were georeferenced, calculating incidence rates for each Milan Municipality. Viral genotypic analysis was carried out. Results:  353 cases were reported in Milan. Incidence rates resulted significantly higher in males (RR 18.1 CI9 5% 11.5 – 28.4). 70 cases reported foreign travel. 172 cases reported “Men  who have Sex with Men” behaviour. Genotypic analysis revealed correlation with strains of the European “Men who have Sex with Men” epidemic. Georeferencing showed asymmetric case distribution. Only 12 cases reported Hepatitis A vaccination. The Relative Risk for syphilis infection among Hepatitis A cases was 133.9 (95% CI 81.7 – 219.7) and 29.7 (95%CI 9.5 – 92.7) for gonorrhea. Conclusions:  Most genotyped cases (93.7%) correlated to the European Hepatitis A epidemic among Men who have Sex with Men. Georeferencing showed a greater incidence of Hepatitis A cases in areas characterized by the homosexual community. The higher incidence of Sexually Transmitted Diseases co-infection in Hepatitis A cases correlated to clusters responsible for the European Hepatitis A epidemic, suggests increased sexual promiscuity among Men who have Sex with Men. These data support the need for Hepatitis A vaccination programs and sensitization of Men who have Sex with Men to the adoption of safe sexual practices.